2019
DOI: 10.1007/s42154-019-00056-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Engine Fuel Injection Studies Using Synchrotron Radiation X-ray Imaging

Abstract: Fuel spray characteristics directly determine the formation pattern and quality of the fuel/air mixture in an engine, and thus affect the combustion process. For this reason, the improvement and optimization of fuel injection systems is crucial to the development of engine technologies. The fuel jet breakup and atomization process is a complex liquid-gas two-phase turbulent flow system that has not yet been fully elucidated. Owing to the limitations of standard optical measurement techniques, the spray breakup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Another effective approach is to measure the transient needle motion using a high-speed X-ray phaseenhanced imaging (XPCI) technique. 30,31 In Kastengren et al, 32 it was found that the maximum lift within the injectors was linearly related to the rail pressure, which is presumed to be related to the elastic deformation of the needle valve. They also measured the maximum and minimum eccentric radial displacement from four different injectors to be 0.065 and 0.016 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Another effective approach is to measure the transient needle motion using a high-speed X-ray phaseenhanced imaging (XPCI) technique. 30,31 In Kastengren et al, 32 it was found that the maximum lift within the injectors was linearly related to the rail pressure, which is presumed to be related to the elastic deformation of the needle valve. They also measured the maximum and minimum eccentric radial displacement from four different injectors to be 0.065 and 0.016 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although such elaborate optical studies on realsize nozzles have been very informative, they mostly allowed interpretation of events on the basis of mere observation, not by truly quantitative information of the flow field, amount of in-nozzle vapour, pressure, temperature, etc., neither by providing conclusive evidence on the exact mechanism of nozzle emptying and air backfilling [19,20]. In recent years, X-ray techniques of real all metal injectors have provided further insights into these complex multiphase flow problems [21,22], including some interpretation of needle motion effects on the in-nozzle flow during injection and at the end of injection with quantification of fuel dripping (e.g. [23,24]).…”
Section: Introduction 1backgroundmentioning
confidence: 99%